The incorporation of the concept of environmental education by the hegemonic discourse around sustainable development - Hermógenes da Silva, Hugo Juliano; Bezerra Bispo, Camilla Beatritse; Spuldaro Tanno, Natália (Sociologias Plurais, 2013)
This essay reports the incorporation of Environmental Education (EE) by the hegemonic discourse of moderate environment and its conversion into Education for Sustainable Development (ESD). To do so, we present both concepts and how they are discussed in specific international conferences. We also use Bourdieu's concept of social and environmental field to demonstrate how hegemonic creative skills devlop in this area. It was concluded that ESD collaborates by reproducing a model of privilege and economic growth at the expense of the ecological and social dimensions of development.